Perlindungan Hukum bagi Debitur dalam Kontrak Standar Perjanjian Bank Garansi - Ajrina Febi; Mohamad Fajri Mekka Putra (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
The absence of a conceptual definition of a Bank Guarantee has resulted in different interpretations from one bank to another in translating the applicable regulations. Some legal experts questioned the standard contract because it is considered not to provide room for negotiation between contracting parties and tends to create an imbalance of rights and obligations between the bank and the debtor customer. The bank guarantee plays a role when the customer defaults on the bank, that is, the bank has the right to exercise, but if the customer avoids it, the second step is for the bank to issue a warning letter. The author focused on standard contracts/agreements regarding bank guarantees. In writing this paper, the issues raised are regarding the legal protection of the parties in a bank guarantee agreement. The research method used is normative law research using normative law case studies in the form of legal behavior products. The practice of fraud, deception, and forgery is one of the legal problems faced by the parties in the Bank Guarantee and Standby L/C agreements. This act of fraud has been proven to have a detrimental effect on both internal and external banking parties. The higher the intensity of fraud, the higher the level of decline in customer trust in banking institutions.